Congenital Haemolytic Anaemia with early onset and uncommon presentation: A Case Report - Fazilatunnesa, -; Ara, Anjuman; Asadujjaman, Mohammad; Jahan, Shahanaz; Hasan, Muhammad Masud; Tamanna, Kishwar Zaman; Begum, Ambia; Ansary, Nahid Bintay (Community Based Medical Journal, 2017)
Haemolytic anaemias result from an increase in the rate of red cell destruction. The lifespan of the normal red cell is 100-120 days; in the haemolytic anaemias it is shortened by varying degrees, and in very severe cases may be only a few days. Here we described a male child of 1.5 months presented with yellow coloration of whole body and sclera since birth, progressive pallor since birth & gradual abdominal distention for 20 days. The child was admitted to hospital with the complaints of bleeding from mouth and nose for 3 days. Peripheral blood film of the child showed features of hemolytic anaemia, as a congenital hemolytic anaemia probably hemoglobinopathies/thalassemia. As because the child is 1.5 months old the diagnosis was confirmed by Hb-electrophoresis of his parents. Hb-electrophoresis examination of the parent showed predominant Hb was HbE which was 90.0% found in mother & 92.4% found in father. So the case was diagnosed as congenital hemolytic anaemia, HbE disease. CBMJ 2017 July: Vol. 06 No. 02 P: 32-37